THE PLACE OF TERMS IN A LITERATURE TEXT (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article explores the role and stylistic possibilities of terms in literary texts, their meaning in scientific discourse, their role as the basis for artistic and figurative expression, and their role as a linguopoetic tool.